Sex differences in the human metabolome - Costanzo, Michele; Caterino, Marianna; Sotgiu, Giovanni; Ruoppolo, Margherita; Franconi, Flavia; Campesi, Ilaria (Biology of sex differences, 2022)
Background The sexual dimorphism represents one of the triggers of the metabolic disparities between the organisms, advising about wild implications in research or diagnostics contexts. Despite the mounting recognition of the importance of sex consideration in the biomedical fields, the identification of male- and female-specific metabolic signatures has not been achieved. Main body This review pointed the focus on the metabolic differences related to the sex, evidenced by metabolomics studies performed on healthy populations, with the leading aim of understanding how the sex influences the baseline metabolome. The main shared signatures and the apparent dissimilarities between males and females were extracted and highlighted from the metabolome of the most commonly analyzed biological fluids, such as serum, plasma, and urine. Furthermore, the influence of age and the significant interactions between sex and age have been taken into account. Conclusions The recognition of sex patterns in human metabolomics has been defined in diverse biofluids. The detection of sex- and age-related differences in the metabolome of healthy individuals are helpful for translational applications from the bench to the bedside to set targeted diagnostic and prevention approaches in the context of personalized medicine. Graphical Abstract Highlights Metabolomics is the gold-standard analytical approach to detect metabolic signatures in human biofluids. Analyzing the metabolome at the baseline in healthy individuals is important to identify metabolite signatures to be attributed to one sex or both. Differences in the metabolome of biofluids are sex- and age-dependent. Sex is not still adequately considered in metabolomics-based investigations.